2008
DOI: 10.1094/cchem-85-2-0140
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Volatiles of Rice During Cooking Analyzed by Modified Headspace SPME/GC‐MS

Abstract: The flavor volatiles in three Japanese rice cultivars, Nihonbare, Koshihikari, and Akitakomachi, during cooking were directly extracted by using a modified headspace solid‐phase microextraction (SPME) method and analyzed by gas chromatography‐mass spectrometry (GC‐MS). A total of 46 components were identified, including aldehydes, ketones, alcohols, and heterocyclic compounds, as well as fatty acids and esters, phenolic compounds, hydrocarbons, etc. The amount of key odorant compounds increased with cooking, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 47 publications
1
46
0
Order By: Relevance
“…21 Direct extraction of volatile compounds of rice during cooking in an automatic rice cooker, using the SPME/GC/MS technique, revealed that 4-vinyl guaiacol was detected during the last 10 min of cooking and also during 30 min of warming in the cooker. 15 The latter results also indicated the thermally induced formation of this compound. A previous study reported an increase in 4-vinyl guaiacol in both hulled and milled rice samples stored in paper bags at 30…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…21 Direct extraction of volatile compounds of rice during cooking in an automatic rice cooker, using the SPME/GC/MS technique, revealed that 4-vinyl guaiacol was detected during the last 10 min of cooking and also during 30 min of warming in the cooker. 15 The latter results also indicated the thermally induced formation of this compound. A previous study reported an increase in 4-vinyl guaiacol in both hulled and milled rice samples stored in paper bags at 30…”
Section: Resultsmentioning
confidence: 80%
“…These volatiles have previously been reported as odour-active compounds of cooked black or white rice of several japonica and indica cultivars 11,12 and/or flavour molecular markers used to differentiate three Japanese rice cultivars. 15 Ten of these compounds have been identified as volatile lipid oxidation products 10,16,17 that may relate to off-flavour of rice samples. Storage time and temperature as well as type of packaging material apparently affected the relative amounts of isolated volatiles from the rice samples (Tables 3-5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rice bran, the outer brown layer that removed during the milling of brown rice, has been extensively studied, of which 4-vinylphenol was the main component having a characteristic unpleasant odor [2][3][4] . Many researchers have studied volatile compound in raw and cooked rice, 2-acetyl-1-pyrroline (2-AP; popcorn aroma) was reported as an important contributor to be the aroma characteristic of rice [5][6][7][8][9] . Straw of rice also reported on volatile components, palmitic acid was the most abundant component, followed by hexahydrofarnesyl acetone and phytol 10) .…”
Section: Introductionmentioning
confidence: 99%